2022
DOI: 10.31223/x50627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A discontinuous Galerkin method for sequences of earthquakes and aseismic slip on multiple faults using unstructured curvilinear grids

Abstract: Physics-based simulations provide a path to overcome the lack of observational data which is hampering a holistic understanding of earthquake faulting and crustal deformation across the vastly varying space-time scales governing the seismic cycle. However, simulations of sequences of earthquakes and aseismic slip (SEAS) including more than one fault, complex geometries, and elastic heterogeneities are challenging. We present a symmetric interior penalty discontinuous Galerkin (SIPG) method to perform SEAS simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…For example, a recent dynamic rupture simulation of the 2008 Wenchuan earthquake (Tang et al., 2021) did not include the Xiaoyudong fault in their multi‐fault system because of numerical stability issues. This problem may be addressed using the discontinuous galerkin (DG) method that better handles fault geometry complexities in dynamic rupture simulations (e.g., Ulrich, Gabriel, et al., 2019; Ulrich, Vater, et al., 2019; Wollherr et al., 2019), and also possibly for quasi‐dynamic earthquake sequence models (e.g., Kozdon et al., 2019; Uphoff et al., 2022). Besides the fault geometrical complexities, previous numerical studies have also indicated that a larger ratio between the width of seismogenic zone and the critical nucleation size ( h *) along with the variation of ( b − a )/ a will introduce more complexities in earthquake cycles and rupture pattern (Barbot, 2019; Cattania, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent dynamic rupture simulation of the 2008 Wenchuan earthquake (Tang et al., 2021) did not include the Xiaoyudong fault in their multi‐fault system because of numerical stability issues. This problem may be addressed using the discontinuous galerkin (DG) method that better handles fault geometry complexities in dynamic rupture simulations (e.g., Ulrich, Gabriel, et al., 2019; Ulrich, Vater, et al., 2019; Wollherr et al., 2019), and also possibly for quasi‐dynamic earthquake sequence models (e.g., Kozdon et al., 2019; Uphoff et al., 2022). Besides the fault geometrical complexities, previous numerical studies have also indicated that a larger ratio between the width of seismogenic zone and the critical nucleation size ( h *) along with the variation of ( b − a )/ a will introduce more complexities in earthquake cycles and rupture pattern (Barbot, 2019; Cattania, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…YATeTo therefore plays two important roles in SeisSol (and in similar applications 26 ): (1) it provides a convenient way for expressing DG-like numerical schemes for various wave propagation models 4,21,22 and (2) it works as an abstract performance portability layer between application and hardware.…”
Section: Yateto Dsl In Seissolmentioning
confidence: 99%
“…The flexibility of domainbased methods allows for handling small-scale heterogeneities, material nonlinearities, as well as complexities of fault geometry (Kuna, 2013;Taborda & Bielak, 2011;Aagaard et al, 2013;Kaneko et al, 2011;Allison & Dunham, 2018;Erickson & Dunham, 2014;Thakur et al, 2020;Barbot, 2019;Mia et al, 2022;Erickson et al, 2017). However, modeling sequences of earthquakes and seismic slip with domain-based methods requires substantial computational effort due to the different spatial, and temporal scales (Tong & Lavier, 2018;Biemiller & Lavier, 2017;Kaneko et al, 2008;Allison & Dunham, 2018;Van Dinther et al, 2013;Mckay et al, 2019;Uphoff et al, 2022). Alternatively, boundary integral techniques reduce the dimensions of the problem by one, limiting the computations to the fault surface; thus, alleviating the computational cost (Aliabadi, 1997;Lapusta et al, 2000;Lapusta & Liu, 2009;Barbot, 2019;Cattania & Segall, 2021;Nie & Barbot, 2022;Heimisson & Rinaldi, 2022).…”
Section: Previous Modelingmentioning
confidence: 99%